Penerapan Konsep Ekonomi Sirkular Dalam Pengelolaan Sampah Untuk Menunjang Green Economy di Desa Nelayan Kondangmerak, Kabupaten Malang - Setyawan, Fahreza Okta; Yona, Defri; Rahman, M. Arif; Firdaus, Naufal; Risqi, Mohammad Aditya (Universitas Pahlawan Tuanku Tambusai, 2024)
Waste management remains a challenge in Indonesia to this day. Several regions, including the fishing village of Kondangmerak in Malang Regency, East Java, still face obstacles in the waste disposal process. Due to its distance from the village's administrative center, 20 households in Kondangmerak are compelled to manage their own waste. Efforts involve waste incineration, but this poses new issues due to incomplete combustion. The objective of this initiative is to enhance the knowledge and well-being of the community through waste management activities. Various methods are employed, such as waste management and recycling training, the creation of plastic bottle waste bins, and the development of infographic banners on waste. The outcomes encompass improved community skills in waste management, the utilization of dedicated plastic waste bins, and the dissemination of information through infographic banners at various locations along the Kondangmerak Beach.